Literatura de cordel na escola: uma proposta de mediação para a formação de leitores em turmas de 8º ano - Santos , José Clovis dos (2024)
Given the problem of teaching reading in basic education (final years) and the teacher's difficulties faced with the limitations of the textbook with regard to teaching literature, as well as the poor performance of students in the class of this subject, the present research is situated in the field of investigations into reader formation through cordel literature. Its general objective is to promote the formation of readers in 8th grade classes of elementary school, through literary literacy, based on the Cordel Paraibano by Leandro Gomes de Barros. The methodology used is field research, qualitative in nature, explanatory and interventionist in nature, with a view to providing students with other possibilities for teaching literature in elementary school. In this way, an action research was carried out, whose data were collected through two questionnaires applied to the research participants, which were later analyzed using qualitative criteria, and participant observation as a way of identifying how these subjects deal with the literary text. in literature class. To prove or refute the success of the method adopted, a basic didactic reading sequence was created, following the guidelines of Rildo Cosson (2021), taking as a reference the cordel História de Juvenal e o Dragão to promote the literary literacy of students at a school municipal public service in the city of Santa Rita - PB. To this end, the research was supported by the contributions of Antonio Cândido (2004), Santos (2016), Maia (2007) and BNCC (2018) on Literature and teaching; Pinheiro (2004) on Literature research; Marinho and Pinheiro (2012) and Negreiros (2016), regarding Cordel Literature; Yala (1995), referring to popular culture; Bragatto and Lajolo (1995), Foucambert and Martins (1994), Silva (2006) and the PCN (1998), on Reading and reader training; Kleiman (1995) and Freire (2002) on Literacy; Cosson (2021), Antonio Candido (2014), Zappone (2008) and Zilberman (1997) regarding literary literacy, in addition to other scholars on the subject cited in this research. As for the method of analyzing the data obtained, the one proposed by Bardin (1977) was used, which helped in understanding the reality researched. The results obtained were significant, as there were advances in the classroom - greater attendance, interest and participation of students in reading and text production activities, with emphasis on listening, speaking and writing skills. It was found that exploring the potential of cordel linked to social literacy practices constitutes an interesting and effective means of promoting literary literacy in literature classes. As a consequence of this, the research teacher is also able to have a more reflective and critical attitude about his own teaching practice and feels motivated to seek ways that help him improve his pedagogical work in order to participate more effectively in the process of student emancipation.